Ovariectomy and obesity have equal impact in causing mitochondrial dysfunction and impaired skeletal muscle contraction in rats - Wissuta Sutham (2018)
OBJECTIVE: Previous studies have demonstrated that either an obese-insulin resistance condition or a condition involving loss of estrogen impaired skeletal muscle function as indicated by a decrease in muscle contraction. The differing effects of combined estrogen deficiency over obese-insulin resistance on skeletal muscle function have, however, not yet been determined. Our hypothesis was that estrogen deficiency aggravates skeletal muscle dysfunction in obese-insulin resistant rats, via increased muscle oxidative stress and mitochondrial dysfunction. METHODS: Twenty-four female Wistar rats were divided into 2 groups and animals in each group were fed either a normal diet (ND) or a high-fat diet (HFD) for 24 weeks. At week 13, rats in each group were subdivided into 2 subgroups: sham-operated or ovariectomized (n = 6/subgroup). At the end of the experimental period the contraction of the gastrocnemius muscles was tested before the rats were sacrificed. Skeletal muscle was removed to assess oxidative stress and mitochondrial function. RESULTS: We found that an obese-insulin resistant condition was observed in sham-operated HFD-fed rats, ovariectomized ND-fed rats, and ovariectomized HFD-fed rats. Skeletal muscle contractile function (peak-force ratio [g/g]; 25.40 ± 2.03 [ovariectomized ND-fed rats], 22.44 ± 0.85 [sham-operated HFD-fed rats] and 25.06 ± 0.61 [ovariectomized HFD-fed rats]), skeletal muscle mitochondrial function, and oxidative stress were equally significantly impaired in all 3 groups, when compared with those of sham-operated ND-fed rats (31.12 ± 1.88 g/g [NDS]; P < 0.05). Surprisingly, loss of estrogen did not aggravate these dysfunctions of skeletal muscles in HFD-fed rats. CONCLUSIONS: These findings suggest that skeletal muscle dysfunction may occur due to increased muscle oxidative stress and mitochondrial dysfunction as a result of ovariectomy and obese-insulin resistance. Loss of estrogen, however, did not aggravate these impairments in the muscle of rats with obese-insulin resistant condition.